A method for preparing spherical TATB-based explosives based on super-hydrophobic effect
By preparing spherical TATB-based explosives using superhydrophobic effects, the problems of binder influence on energy and weak interfacial bonding in existing methods are solved. This allows for the control of morphology and size, improves flowability and mechanical properties, and makes the explosives suitable for large-scale production.
Patent Information
- Application Number
- CN202610625342.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-08
- Publication Date
- 2026-06-16
AI Technical Summary
In existing methods for preparing TATB-based explosives, the use of non-energetic binders leads to reduced energy, complex processes, uneven powder morphology, and poor flowability. Furthermore, the weak interfacial bonding between non-energetic polymer binders and TATB particles affects the mechanical strength and long-term aging performance of the explosive charge.
A method for preparing spherical TATB-based explosives using the superhydrophobic effect involves mixing a binder with TATB, melting the mixture on the surface of a superhydrophobic anti-sticking release agent, and allowing it to spontaneously aggregate into spheres. Combined with programmed cooling, filtration, and drying steps, spherical explosives with uniform particle size are prepared.
The morphology and size of TATB-based explosives were controlled, the energy performance of the samples was maintained, and the flowability and mechanical properties were improved. The process is simple, low-cost, and suitable for large-scale production.
Smart Images

Figure CN122212880A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of energetic material modification technology. More specifically, this invention relates to a method for preparing spherical TATB-based explosives based on superhydrophobic effects. Background Technology
[0002] 1,3,5-Triamino-2,4,6-Trinitrobenzene (TATB) is a high-energy explosive with extremely low sensitivity to heat, impact, friction, and electrical sparks. As an insensitive explosive, TATB is widely used in military fields such as weapons and ammunition, and propellants. Currently, the molding of TATB-based explosives almost entirely relies on polymer-bonded explosives (PBX) technology. This technology typically involves mixing, coating, and granulating ultrafine TATB powder with a non-energetic polymer binder through a solvent-water suspension process, and finally molding it by compression. While this method can produce explosive components with good performance, the introduction of the non-energetic binder reduces the system energy and is accompanied by process complexity and environmental issues. In addition, the molded powder has an uneven morphology and poor flowability; more importantly, the interfacial bonding between the non-energetic polymer binder and TATB particles is weak, which may impair the mechanical strength and long-term aging performance of the explosive charge. Therefore, it is essential to develop a novel process for preparing spherical TATB-based explosives.
[0003] Jing et al. successfully prepared TATB-based energetic composite microspheres using a self-designed continuous pipeline self-assembly device with ethyl acetate (EA) as solvent and fluororubber (F2602) and nitrocellulose (NC) as binders. Experiments showed that when the ratio of NC to F2602 was 2.5%, microspheres with smooth surfaces, good sphericity, and dense interiors were obtained. This technique preserves the crystal structure and thermal stability of TATB, reduces its mechanical sensitivity, and significantly improves the flowability of the molded powder and the mechanical properties of the compressed pharmaceutical column. However, the addition of non-energetic components affects the performance of the final product, and the real-time precise control of microsphere size still highly depends on the online adjustment of the pump flow rate. This strategy places high demands on process control precision and may face cost-effectiveness challenges in large-scale applications (Chemical Engineering Journal, 2023, 471).
[0004] Liu et al. prepared TATB-based PBX explosives using five fluoropolymers with different molecular structures as binders. They systematically compared the effects of the binders on the properties of the explosives. The experiments revealed that the C-Cl bonds (derived from CTFE monomers) in the binder molecular structure play a key role in maintaining polymer stiffness and improving PBX strength. Using CTFE-containing fluoropolymers as binders can significantly improve the static mechanical strength, dynamic mechanical properties, and creep resistance of TATB-based PBXs. However, in-depth research on the optimal molecular structure and ratio of binders, interfacial interaction mechanisms, etc., is still insufficient. Furthermore, the molding processability of some fluoropolymers is poor, and their industrial application still faces challenges. (Propellants, Explosives, Pyrotechnics, 2018, 43(7):664-670.) Lin et al. used the water suspension method to modify TATB-based polymer-bonded explosives by adding different amounts (0.05wt%~0.5wt%) of graphene, and systematically studied the nonlinear viscoelastic properties of the composite material. Experiments showed that the introduction of a small amount of graphene significantly improved the storage modulus, static mechanical properties, and creep resistance of PBX. This study provides an effective way to improve the mechanical properties of PBX through nanofiller modification. However, the uniformity of graphene dispersion in the matrix, the agglomeration effect at high graphene content, and its long-term service performance in actual weapon systems still require further investigation (Composites Science and Technology, 2018, 160152-160).
[0005] The methods for preparing TATB-based explosives reported in these documents have certain shortcomings in terms of binder selection and preparation processes. Therefore, designing and inventing new preparation processes for TATB-based explosives to meet the needs of industrial production is an urgent technical problem to be solved in this field. Summary of the Invention
[0006] One object of the present invention is to solve at least the above-mentioned problems and / or defects, and to provide at least the advantages described below.
[0007] To achieve these and other advantages according to the present invention, the present invention provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, comprising the following steps: Step 1: Heat the adhesive to a molten state in a water bath, add TATB to the molten adhesive, stir to mix the two components evenly, and then cool down until the mixture solidifies to obtain a TATB-adhesive mixture. Step 2: Cut the TATB-adhesive mixture into the required size, place it on the surface of the superhydrophobic anti-stick release agent, and heat it in a water bath until the TATB-adhesive mixture melts. Utilize the superhydrophobic interface effect to cause the molten material to spontaneously aggregate into spheres with uniform particle size. Then, cool it down in a programmed manner until the spheres are completely solidified. Step 3: The solidified product is filtered, washed, and dried to obtain spherical TATB-based explosive.
[0008] Preferably, in step one, the adhesive is one or more of paraffin, TNT, DNAN, tetranitroerythritol, and 2-methyl-4,6-dinitroanisole.
[0009] Preferably, in step one, the water temperature in the water bath is raised to 20°C to 100°C.
[0010] Preferably, in step one, the mass ratio of the adhesive to TATB is 1:1 to 1:10.
[0011] Preferably, in step one, the cooling rate is 0.1℃ / min to 2℃ / min.
[0012] Preferably, in step two, the TATB-binder mixture has a cutting particle size of 400μm to 2000μm.
[0013] Preferably, in step two, the superhydrophobic anti-stick release agent is selected from one or more of polyethylene wax, zinc stearate, fluoropolymer coating, perfluoroethylene propylene, liquid paraffin, butyl stearate, and polytetrafluoroethylene.
[0014] Preferably, in step two, the water temperature in the water bath is raised to 20°C to 100°C.
[0015] Preferably, in step two, the rate of temperature reduction is 0.1℃ / min to 2℃ / min.
[0016] Preferably, in step three, the washing process uses one or more of distilled water, ethanol, dimethyl sulfoxide, and ethyl acetate, and the drying method is one of room temperature drying, vacuum drying, or freeze drying.
[0017] In step two, the superhydrophobic anti-sticking release agent is replaced with an equal mass of fluorinated graphene-modified polytetrafluoroethylene powder. The preparation method of the fluorinated graphene-modified polytetrafluoroethylene powder includes: S1. Load polytetrafluoroethylene powder into the plasma powder reaction chamber, evacuate to below 5 Pa, and introduce a mixed gas of CF4 and Ar in a volume ratio of 1:3 at a flow rate of 30~50 sccm; set the parameters: radio frequency power 40~80W, processing time 60~120s to obtain activated polytetrafluoroethylene powder.
[0018] S2. Add fluorinated graphene powder to anhydrous ethanol and sonicate for 20-40 min until completely dispersed to obtain a fluorinated graphene dispersion. Add tridecafluorooctyltrimethoxysilane to the fluorinated graphene dispersion, sonicate for 30 min, then heat to 50-60℃ and keep warm for 20-40 min. Cool to room temperature for later use. The ratio of fluorinated graphene, tridecafluorooctyltrimethoxysilane to anhydrous ethanol is 1-10 g: 0.05-0.1 g: 500 mL. S3. Add activated polytetrafluoroethylene powder to a fluidized bed. The mass of activated polytetrafluoroethylene powder is 10 to 40 times the mass of fluorinated graphene powder. Purge with nitrogen gas (flow rate 0.2 m / s) to make the powder fully suspended in a fluidized state. Spray the fluorinated graphene dispersion evenly into the fluidized bed through an atomizer and react at a constant temperature of 30 to 60°C for 20 to 40 minutes. Raise the temperature to 80 to 90°C and continuously purge with nitrogen gas for 5 to 20 minutes to remove residual solvent. Take out the powder and vacuum dry it at 60 to 80°C for 2 to 4 hours. Pass it through a 200-mesh sieve to obtain fluorinated graphene-modified polytetrafluoroethylene powder.
[0019] The present invention has at least the following beneficial effects: (1) Based on the superhydrophobic effect, the present invention can simultaneously control the morphology and size of TATB-based explosives. Compared with other methods, the binder selected in the present invention is an energetic component, which does not reduce the sample energy and can achieve kilogram-scale preparation. In addition, the anti-sticking release agent selected in the present invention has low cost and simple process.
[0020] (2) The present invention controls the size of spherical TATB-based explosives, and the particle size range is adjustable within 200μm~2000μm. The prepared sample has good flowability, and its crystal form and structure have not changed. The thermal decomposition performance is improved, and the mechanical properties of TATB are greatly improved.
[0021] (3) In the process of preparing spherical TATB, the present invention uses fluorinated graphene-modified polytetrafluoroethylene powder to replace polytetrafluoroethylene powder. The fluorinated graphene-modified polytetrafluoroethylene powder has better hydrophobic and anti-stick properties. Using fluorinated graphene-modified polytetrafluoroethylene powder as a superhydrophobic anti-stick release agent significantly improves the sphericity of spherical TATB.
[0022] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description
[0023] Figure 1 This is a scanning electron microscope image of the raw material TATB; Figure 2 This is a scanning electron microscope image of the TATB sample prepared in Example 1 of the present invention at a scale of 200 μm. Figure 3 This is a scanning electron microscope image of the TATB sample prepared in Example 1 of the present invention at a scale of 100 μm. Figure 4 This is a scanning electron microscope image of the TATB sample prepared in Example 1 of the present invention at a scale of 10 μm. Figure 5 The XRD patterns are of the TATB sample prepared in Example 1 of this invention and the raw material TATB. Figure 6 The images show the FT-IR spectra of the TATB sample prepared in Example 1 of this invention and the raw material TATB. Figure 7 The images show the DSC diagrams of the TATB sample prepared in Example 1 of this invention and the raw material TATB. Figure 8 This is a photograph of the TATB sample prepared in Example 1 of the present invention; Figure 9 This is a photograph of the TATB sample prepared in Comparative Example 1 of this invention. Detailed Implementation
[0024] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.
[0025] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof. Example 1: This embodiment provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, including the following steps: Step 1: Weigh 0.2g of trinitrotoluene (TNT), heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.6g of TATB, stir and mix evenly, and cool it down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with different particle sizes, place them on polytetrafluoroethylene powder, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to solidify the mixture again. Step 3: Wash and dry to obtain spherical TATB-based explosives.
[0026] Figure 1 This is a scanning electron microscope image of the raw material TATB; Figure 2 The images show scanning electron microscope (SEM) images of spherical TATB-based explosives with particle sizes of approximately 700 μm, 1100 μm, and 1700 μm (with an error of 100 μm) prepared in this embodiment, with sphericity between 0.85 and 0.92. Figure 3 This is a scanning electron microscope (SEM) image of the surface of the spherical TATB-based explosive prepared in Example 1. Figures 1-4 It can be seen that the raw material TATB has an irregular crystal shape, a wide particle size distribution, a rough surface, and an irregular layered structure. The TATB-based explosive prepared in Example 1 is a perfect sphere with a smooth surface. Depend on Figure 5 It can be seen that the characteristic diffraction peaks of the raw material TATB are located at 11.3°, 19.6°, 28°, and 42.1°, while the characteristic diffraction peaks of the raw material TNT are located at 12.5°, 15.6°, 22.9°, 29.6°, and 33.3°. The spherical TATB-based explosive prepared in Example 1 basically matches the characteristic diffraction peak positions of the two raw materials, indicating that the prepared spherical TATB-based explosive did not change the crystal form of the raw materials; Figure 6 It can be seen that the raw material TATB is at 3321.2cm. -1 With 3215.2cm -1 The peak represents the asymmetric and symmetric stretching vibrations of -NH3, at 1604.7 cm⁻¹. -1 With 1450.6cm -1 This is the vibrational absorption peak of the -C=C- skeleton on the benzene ring, at 1230.5 cm⁻¹. -1 With 1189.9cm -1 The absorption peak is due to the stretching vibration of -NO2; the raw material TNT has an absorption peak at 1537.2 cm⁻¹. -1 With 1591.7cm -1 The characteristic absorption peak of the benzene ring is 906.5 cm⁻¹. -1 Generated by -CH3 vibration, 792.8 cm -1 The absorption peak is the -NO2 shear vibration peak, 712 cm⁻¹. -1 The absorption peak is the -NO2 shear vibration peak. The absorption peak of the spherical TATB-based explosive is a simple superposition of TATB and TNT, and no new absorption peak appears, indicating that no chemical reaction occurs between the two to generate new substances during the preparation of the spherical TATB-based explosive.
[0027] Figure 7It can be seen that the TNT raw material exhibits two endothermic peaks at 82.6℃ and 249.9℃, while the TATB raw material exhibits two exothermic peaks at 358.3℃ and 368.3℃. The prepared spherical TATB-based explosive sample exhibits two endothermic peaks at 82.5℃ and 221.4℃, and two exothermic peaks at 360.1℃ and 369.7℃. The characteristic peak positions of the sample are basically consistent with those of the raw materials TNT and TATB, indicating that TNT and TATB form a homogeneous solid solution with excellent thermal stability and have very good chemical compatibility.
[0028] Example 2: This embodiment provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, including the following steps: Step 1: Weigh 0.2g TNT, heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.6g TATB, stir and mix evenly, and cool down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with different particle sizes, place them on polytetrafluoroethylene powder, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to solidify the mixture again. Step 3: Wash and dry to obtain spherical TATB-based explosives with a particle size of approximately 1500 μm.
[0029] Example 3: This embodiment provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, including the following steps: Step 1: Weigh 0.2g TNT, heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.6g TATB, stir and mix evenly, and cool down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with different particle sizes, place them on polytetrafluoroethylene powder, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to solidify the mixture again. Step 3: Wash and dry to obtain spherical TATB-based explosives with a particle size of approximately 450 μm.
[0030] Example 4: This embodiment provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, including the following steps: Step 1: Weigh 0.2g TNT, heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.6g TATB, stir and mix evenly, and cool down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with different particle sizes, place them on polytetrafluoroethylene powder, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to solidify the mixture again. Step 3: Wash and dry to obtain spherical TATB-based explosives with a particle size of approximately 700 μm.
[0031] Example 5: This embodiment provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, including the following steps: Step 1: Weigh 0.2g TNT, heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.4g TATB, stir and mix evenly, and cool down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with different particle sizes, place them on polytetrafluoroethylene powder, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to solidify the mixture again. Step 3: Wash and dry to obtain spherical TATB-based explosives with a particle size of approximately 900 μm.
[0032] Example 6: This embodiment provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, including the following steps: Step 1: Weigh 0.2g TNT, heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.6g TATB, stir and mix evenly, and cool down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with different particle sizes, place them on polyethylene wax powder, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to allow the mixture to solidify again. Step 3: Wash and dry to obtain spherical TATB-based explosives with a particle size of approximately 2000 μm.
[0033] Example 7: This embodiment provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, including the following steps: Step 1: Weigh 0.2g TNT, heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.6g TATB, stir and mix evenly, and cool down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with different particle sizes, place them on zinc stearate powder, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to allow the mixture to solidify again. Step 3: Wash and dry to obtain spherical TATB-based explosives with a particle size of approximately 1750 μm.
[0034] Example 8: This embodiment provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, including the following steps: Step 1: Weigh 0.2g TNT, heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.6g TATB, stir and mix evenly, and cool down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with different particle sizes, place them on polytetrafluoroethylene powder, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to solidify the mixture again. Step 3: Wash and dry to obtain spherical TATB-based explosives with a particle size of approximately 1120 μm.
[0035] Example 9: This embodiment provides a method for preparing spherical TATB-based explosives based on superhydrophobic effects, including the following steps: Step 1: Weigh 0.2g TNT, heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.6g TATB, stir and mix evenly, and cool down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with varying particle sizes, place them on liquid paraffin, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to allow the mixture to solidify again. Step 3: Wash and dry to obtain spherical TATB-based explosives with a particle size of approximately 640 μm.
[0036] Example 10: The difference between this embodiment and Embodiment 1 is that, in step two of this embodiment, the polytetrafluoroethylene powder is replaced with an equal mass of fluorinated graphene-modified polytetrafluoroethylene powder. The preparation method of the fluorinated graphene-modified polytetrafluoroethylene powder includes: S1. Load polytetrafluoroethylene powder into the plasma powder reaction chamber, evacuate to 2 Pa, and introduce a mixed gas of CF4 and Ar with a volume ratio of 1:3 at a flow rate of 50 sccm. Set the parameters: RF power 80W, processing time 120s to obtain activated polytetrafluoroethylene powder.
[0037] S2. Add 1g of fluorinated graphene powder to 100mL of anhydrous ethanol, sonicate for 30min until completely dispersed to obtain a stable fluorinated graphene dispersion; add 0.01g of tridecafluorooctyltrimethoxysilane to the fluorinated graphene dispersion, sonicate for 30min, then heat to 60℃, keep warm for 30min, and cool to room temperature for later use. S3. Add 10g of activated polytetrafluoroethylene powder to a fluidized bed and purge with nitrogen (flow rate 0.2m / s) to make the powder fully suspended in a fluidized state. Spray the fluorinated graphene dispersion evenly into the fluidized bed through an atomizer and react at a constant temperature of 60℃ for 30min. Raise the temperature to 80℃ and purge with nitrogen for 10min to remove residual solvent. Take out the powder, vacuum dry at 80℃ for 4h, and pass it through a 200-mesh sieve to obtain fluorinated graphene-modified polytetrafluoroethylene powder.
[0038] The process parameters for the remaining steps in this embodiment are the same as those in Embodiment 1.
[0039] In this embodiment, the irregular shape of the cut mixture in step two is consistent with that in Example 1, and finally spherical TATB-based explosives with particle sizes of approximately 700 μm, 1100 μm, and 1700 μm are obtained, with a sphericity distribution range of 0.88 to 0.97.
[0040] The main reason for the different particle sizes of the spherical TATB-based explosives obtained in each embodiment is the difference in the size of the irregular shapes cut in step two.
[0041] Comparative Example 1: Step 1: Weigh 0.2g TNT, heat it in a water bath to 80℃ until the TNT is completely melted, then add 0.6g TATB, stir and mix evenly, and cool down at a rate of 0.1℃ / min until the mixture solidifies; Step 2: Cut the mixture into irregular shapes with different particle sizes, place them on a stainless steel plate, heat in a water bath until the mixture melts again, stop heating, and cool down at a rate of 0.1℃ / min to allow the mixture to solidify again. Step 3: Washing and drying to obtain quasi-spherical TATB-based explosives with a particle size of approximately 2000 μm. The particle size of the quasi-spherical TATB-based explosives is distributed between 1500 and 2400 μm, and the sphericity ranges from 0.71 to 0.83.
[0042] Depend on Figure 8 , Figure 9It can be seen that the TATB-based explosive prepared in Comparative Example 1 has a spherical morphology, unlike the regular spherical morphology of the sample prepared in Example 1. Analysis suggests that the extremely low surface energy of the polytetrafluoroethylene used in Example 1 prevents the molten TNT from wetting the PTFE surface, causing it to tend to shrink into a spherical shape, thus forming a perfectly spherical TATB-based explosive. In contrast, the high surface energy of ordinary stainless steel plates results in poor shrinkage of the molten TNT, ultimately preventing the formation of a perfectly spherical TATB-based explosive.
[0043] The number of devices and processing scale described herein are for the purpose of simplifying the description of the invention. Applications, modifications, and variations of the invention will be readily apparent to those skilled in the art.
[0044] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. A method for preparing spherical TATB-based explosives based on superhydrophobic effects, characterized in that, Includes the following steps: Step 1: Heat the adhesive to a molten state in a water bath, add TATB to the molten adhesive, stir to mix the two components evenly, and then cool down until the mixture solidifies to obtain a TATB-adhesive mixture. Step 2: Cut the TATB-adhesive mixture into the required size, place it on the surface of the superhydrophobic anti-stick release agent, and heat it in a water bath until the TATB-adhesive mixture melts. Utilize the superhydrophobic interface effect to cause the molten material to spontaneously aggregate into spheres with uniform particle size. Then, cool it down in a programmed manner until the spheres are completely solidified. Step 3: The solidified product is filtered, washed, and dried to obtain spherical TATB-based explosive.
2. The method for preparing spherical TATB-based explosives based on superhydrophobic effect according to claim 1, characterized in that, In step one, the adhesive is one or more of paraffin, TNT, DNAN, tetranitroerythritol, and 2-methyl-4,6-dinitroanisole.
3. The method for preparing spherical TATB-based explosives based on superhydrophobic effect according to claim 1, characterized in that, In step one, the water temperature in the water bath is raised to 20℃~100℃.
4. The method for preparing spherical TATB-based explosives based on superhydrophobic effect according to claim 1, characterized in that, In step one, the mass ratio of the adhesive to TATB is 1:1 to 1:
10.
5. The method for preparing spherical TATB-based explosives based on superhydrophobic effect according to claim 1, characterized in that, In step one, the cooling rate is 0.1℃ / min to 2℃ / min.
6. The method for preparing spherical TATB-based explosives based on superhydrophobic effect according to claim 1, characterized in that, In step two, the TATB-binder mixture has a cutting particle size of 400~2000μm.
7. The method for preparing spherical TATB-based explosives based on superhydrophobic effect according to claim 1, characterized in that, In step two, the superhydrophobic anti-sticking release agent is selected from one or more of polyethylene wax, zinc stearate, fluoropolymer coating, perfluoroethylene propylene, liquid paraffin, butyl stearate, and polytetrafluoroethylene.
8. The method for preparing spherical TATB-based explosives based on superhydrophobic effect according to claim 1, characterized in that, In step two, the water temperature in the water bath is raised to 20℃~100℃.
9. The method for preparing spherical TATB-based explosives based on superhydrophobic effect according to claim 1, characterized in that, In step two, the cooling rate is 0.1℃ / min to 2℃ / min.
10. The method for preparing spherical TATB-based explosives based on superhydrophobic effect according to claim 1, characterized in that, In step three, the washing process uses one or more of distilled water, ethanol, dimethyl sulfoxide, and ethyl acetate, and the drying method is one of room temperature drying, vacuum drying, or freeze drying.